Effect of Alᶟ⁺ substitutions at Cu-site and AI₂O₃ addition on ultrasonic velocities and elasticanomalies of EuBa₂Cu₃O₇-ᵟ superconductor / Mohd Muzammir Firdaus Abu Bakar - Abu Bakar, Mohd Muzammir Firdaus (2013)
The ultrasonic longitudinal and shear velocities were measured in EuBa₂Cu₃O₇₋₈ (δ = 0.1 and 0.7), EuBa₂Cu₃₋ₓA1ₓO₇₋₈ (х = 0.06 and 0.1) and EuBa₂Cu₃O₇₋₈ + yA1₂O₃ (y = 0.2 and 0.1 wt%) superconductors in temperature ranges of 80-280K and 80-220K, respectively. For EuBa₂Cu₃O₇₋₈ (δ = 0.1 and 0.7), samples, the absolute velocity (at 80K) showed to decrease when the oxygen content was reduced from O6.9 to O6.3 . However, for EuBa₂Cu₃₋ₓA1ₓO₇₋₈ (х = 0.06 and 0.1)) samples, although both samples have same oxygen content (O6.8), the absolute velocity also showed to decrease when the amount of A1ᶟ⁺ increased…